2016
DOI: 10.1111/joic.12263
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Operators’ Height on Individual Radiation Exposure Measurements During Catheter‐Based Cardiovascular Interventions

Abstract: This study suggests that the height from radiation source does impact the measured dose from an operator worn personal TLD. This was operator specific, consistent thought-out multiple procedures, and confined with phantom measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
2
7
1
Order By: Relevance
“…This study did not find a significant correlation between the heights of nursing staff and head dose which reflects the findings by Antic et al, (2013), but contradicts clinical and phantom studies which found that dosimeters worn at chest level detected higher levels of radiation in short staff members than in their taller colleagues (Omar, Marteinsdottir, Kadesjo, & Fransson, 2015;Rigatelli et al, 2016).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This study did not find a significant correlation between the heights of nursing staff and head dose which reflects the findings by Antic et al, (2013), but contradicts clinical and phantom studies which found that dosimeters worn at chest level detected higher levels of radiation in short staff members than in their taller colleagues (Omar, Marteinsdottir, Kadesjo, & Fransson, 2015;Rigatelli et al, 2016).…”
Section: Discussioncontrasting
confidence: 84%
“…It has been reported that staff height may also influence occupational dose as the taller the staff member is, the further away their head is from the source of scattered radiation (Principi et al, ). This study did not find a significant correlation between the heights of nursing staff and head dose which reflects the findings by Antic et al, (), but contradicts clinical and phantom studies which found that dosimeters worn at chest level detected higher levels of radiation in short staff members than in their taller colleagues (Omar, Marteinsdottir, Kadesjo, & Fransson, ; Rigatelli et al, ).…”
Section: Discussionsupporting
confidence: 60%
“…Some authors investigated dose in relation to proximity to the x‐ray tube . Explanatory diagrammatic representation of the position of staff was provided in several articles which allows comparison by dosimetric location rather than assigned role. Specific articulation of staff distances from the x‐ray tube or table was constructive when comparing occupational doses.…”
Section: Methodsmentioning
confidence: 99%
“…This can be explained by the distribution of scatter radiation. Therefore, it is important for dosimeters to always be worn in the same representative position, e. g. on the breast pocket [60]. As shown in ▶ Table 1, there are different dose limits for different organs and body regions.…”
Section: Dosimeter Positionmentioning
confidence: 99%